0489 Sleep Disordered Medicine: A Residents Perspective. (25th May 2022) - Mull, Eric; Pinto, Swaroop
Abstract: Introduction: It is known that sleep medicine is a relatively young subspeciality when compared to other more establish subspecialities, such as cardiology or intensive care medicine. The field gained noticeable recognition following the introduction of positive pressure therapy as a noninvasive method to treat obstructive sleep apnea in 1981. That new method prompted an increased interest in the area of sleep apnea and in all sleep disorders in general. For over the past four decades, sleep medicine has evolved greatly and grown significantly enough to justify the recognition of sleep medicine as an independent specialty.[1] Currently, it is considered a subspeciality that is devoted to the diagnosis and therapy of sleep disorders, which left untreated could increase the risk of chronic medical problems, such as obesity, heart disease, type 2 diabetes, depression, and stroke.[3] There are a limited number of board-certified sleep medicine physicians in the United States to date. According to the National Resident Matching Program (NRMP), there are only 88 accredited training programs accepting candidates for a total of 179 positions. The match result statistics for 2020 showed that out of those 179 openings, only 165 were filled or a 92.2% match rate.[4] The purpose of this quality improvement project was to modify and implement an effective sleep medicine curriculum in an effort to increase residents' awareness and knowledge of the field. With an increased awareness and interest, there was a secondary goal of implementing the project across different academic medical centers. This may ultimately lead to an increase in match rates and having more accredited training programs in the US. Methods: The data presented represents survey responses of medical resident trainees from a single academic medical center, Nationwide Children's Hospital (NCH) in Columbus, Ohio. It is large teaching hospital with 129 categorical pediatric residents and 40 combined internal medicine and pediatric residents. This QI project followed the Plan-Do-Study-Act (PDSA) Cycle, which is a four-stage problem solving model classically used for improving a process or carrying out change. In order to commence this cycle, a key driver diagram was completed (Figure 1). This is a tool to assist in organizing your ideas and discover various causes that contribute to the issues targeted for improvement. The key driver divides the aim of the project into primary and secondary drivers, which represent outcomes and interventions respectively. Primary drivers are factors that are part of the system that directly impacts the aim of this QI project. Secondary drivers are opportunities for change or interventions in this effort. A survey was created with the assistance of division members of the sleep medicine program here at NCH. Once finalized and given that the study focused on the responses of current pediatric resident trainees, it was sent to the Pediatric Residency Graduate Medical Education (GME) Department for appraisal prior to its dissemination. The finalized survey had 29 fields for completion divided over 3 pages to allow for partial completion, although complete completion was desired. Time allotted to the recipients was month duration with two reminder notices. Results: There were a total of 61 respondents that completed and returned the survey out of a total 169 recipients that received the survey. Proportionately, the breakdown of the combined residency program vs. the categorical pediatrics of the respondents was similar to the group at whole, representing 23% and 77% respectively. The level of training was fairly comparable between postgraduate year (PGY) 1 and 3 at 25%, with an increase of the PGY 2 respondents (42.6%) and lowest comprising PGY 4 at only 3.3% of the responses received. Of the 38 trainees that completed elective rotations in pulmonary and neurology, only 2 (3.3%) participated in the formal sleep medicine clinic at the time the survey was disseminated to them. All 61 participants stated that at NCH does not require a sleep medicine rotation and only 3 (4.9%) have completed one. The survey results were reflective of a deficit in didactic sleep medicine instruction, with no respondents stating they received over 3 hours per any academic year. The quality of the instruction was responded as inadequate or poor at 71.4%. The reasoning behind the inadequate to poor instructional response was believed to be due to a simple lack of didactics at 51.3% or just an overall low priority from GME at 46.2%. When asked if they would like to increase the amount of sleep medicine education, 77.6% responded, "Yes, " only one stated, "No, " and the rest responded indifferently. A majority of participants reported that patients inquire the most about sleep medicine during their primary care rotations (93.1%). Although when asked which department should be the most significant in sleep medicine education, there was a relatively even split in the responses received. A slight majority of participants believed it was the responsibility of the outpatient elective rotations to require Sleep Medicine, Pulmonology, Neurology, Psychiatry, and Developmental Pediatrics instruction at 41.1%, followed by Ambulatory clinical participation at 30.4%, and Inpatient Pulmonary or Critical Care at 28.6% throughout the duration of and for the comprehensive completion of their residency program. Conclusion: It is apparent that there are limitations to the educational opportunities for trainees in sleep medicine that are perceived to be multifactorial. The fact that there are a limited number of board-certified sleep medicine physicians in the US may be attributed to the lack of exposure and interest, as well as the absence of a sound educational curriculum that not only may increase the trainees' awareness in the field of study, but provide a comprehensive educational curriculum for sleep medicine instruction to be effectively implemented. With the requirements for trainees to have service rotations in the field of sleep medicine, this may lead to a higher interest and an increased match rate in sleep medicine, resulting in more board-certified physicians within the US. Due to the expanding number of individuals that suffer from sleep apnea and/or other sleep disorders, there is a need to have highly trained board-certified physicians to identify and treat these patients with chronic sleep disorders. In summary, the responses obtained and analyzed from the residents' surveys at NCH conveyed that there is an increasing interest from them for more exposure and instruction in sleep medicine and a need to have a sound educational curriculum to expose and instruct them in the field. The faculty and fellows at NCH have identified this need and implemented the necessary resources to provide additional and vital education to the institution's medical trainees. Support (If Any):